A Mechanistic Study on Reactions of Group 13 Diyls LM with Cp*SbX2: From Stibanyl Radicals to Antimony Hydrides. Issue 59 (11th September 2020) - Helling, Christoph; Wölper, Christoph; Cutsail, George E.; Haberhauer, Gebhard; Schulz, Stephan
Abstract: Oxidative addition of Cp*SbX2 (X=Cl, Br, I; Cp*=C5 Me5 ) to group 13 diyls LM (M=Al, Ga, In; L=HC[C(Me)N (Dip)]2, Dip=2, 6‐ i Pr2 C6 H3 ) yields elemental antimony (M=Al) or the corresponding stibanylgallanes [L(X)Ga]Sb(X)Cp* (X=Br 1, I 2 ) and ‐indanes [L(X)In]Sb(X)Cp* (X=Cl 5, Br 6, I 7 ). 1 and 2 react with a second equivalent of LGa to eliminate decamethyl‐1, 1'‐dihydrofulvalene (Cp*2 ) and form stibanyl radicals [L(X)Ga]2 Sb . (X=Br 3, I 4 ), whereas analogous reactions of 5 and 6 with LIn selectively yield stibanes [L(X)In]2 SbH (X=Cl 8, Br 9 ) by elimination of 1, 2, 3, 4‐tetramethylfulvene. The reactions are proposed to proceed via formation of [L(X)M]2 SbCp* as reaction intermediate, which is supported by the isolation of [L(Cl)Ga]2 SbCp (11, Cp=C5 H5 ). The reaction mechanism was further studied by computational calculations using two different models. The energy values for the Ga‐ and the In‐substituted model systems showing methyl groups instead of the very bulky Dip units are very similar, and in both cases the same products are expected. Homolytic Sb−C bond cleavage yields van der Waals complexes from the as‐formed radicals ([L(Cl)M]2 Sb . and Cp* . ), which can be stabilized by hydrogen atom abstraction to give the corresponding hydrides, whereas the direct formation of Sb hydrides starting from [L(Cl)M]2 SbCp* via concerted β‐H elimination is unlikely. The consideration of the bulky Dip units reveals that the amount of the steric overload in the intermediate I determines the product formation (radical vs. hydride). Abstract : It's radical : Reactions of Cp*SbX2 with LM (M=Ga, In) either selectively yielded Sb‐centered radicals [L(X)Ga]2 Sb . or Sb hydrides [L(X)In]2 SbH. The unexpected formation of Sb hydrides is the result of different steric congestion from the [L(X)M] ligands as was proven by computational calculations.